Plant hairy root cultures as plasmodium modulators of the slime mold emergent computing substrate Physarum polycephalum - Ricigliano, Vincent; Chitaman, Javed; Tong, Jingjing; Adamatzky, Andrew; Howarth, Dianella G. (Frontiers in Microbiology, 2015)
Roots of the medicinal plant Valeriana officinalis are well studied for their various biological activities. We applied genetically transformed V. officinalis root cultures to exert control of Physarum polycephalum, an amoeba-based emergent computing substrate. The plasmodial stage of the P. polycephalum life cycle constitutes a single, multinucleate cell visible by unaided eye. The plasmodium modifies its network of oscillating protoplasm in response to spatial configurations of attractants and repellents, a behavior that is interpreted as biological computation. To program the computing behavior of P. polycephalum, a diverse and sustainable library of plasmodium modulators is required. Hairy roots produced by genetic transformation with Agrobacterium rhizogenes are a metabolically stable source of plant natural products. Adventitious roots were induced on in vitro V. officinalis plants following infection with A. rhizogenes. A single hairy root clone was selected for massive propagation and the biomass was characterized in P. polycephalum chemotaxis, maze-solving, and electrical activity assays. The Agrobacterium-derived roots of V. officinalis elicited a positive chemotactic response and augmented maze-solving behavior. In a simple plasmodium circuit, introduction of hairy root biomass stimulated the oscillation patterns of slime mold’s surface electrical potential. We propose that manipulation of P. polycephalum with the V. officinalis root culture platform can be applied to the development of slime mold microfluidic devices as well as future models for engineering the plant rhizosphere.